The linguistic construction of reality: Toshihiko Izutsu’s semantic hermeneutics of the Qur’ānic Weltanschauung - Solihu, Abdul Kabir Hussain (IIUM Press, 2010)
Toshihiko Izutsu introduces semantic structural analysis to study the structures of the Qur‟ānic worldview. According to this theory of analysis, each language contains a peculiar weltanschauung which causes its speakers to view the world in a way different from the speakers of other languages. Thus by analytic study of the conceptual key-terms of a given language, it is possible to grasp the weltanschauung of the people who use that language as a tool of conceptualizing and interpreting the world in which they live. He employs this semantic theory to examine how the Qur‟ānic key-terms and its particular linguistic categorization of nonlinguistic reality represent subjectively its weltanschauung and its vision of reality. Such semantic approach to the Qur‟ān indicates that its Arabic language is internally coherent, a self-sufficient system of words into which all words have been integrated with an entirely new systemic interpretation; yet it is culturally and historically conditioned, from Jāhilī (pre-Islamic) period to Qur‟ānic era, and thus it is a subjective elaboration of reality. The focus of the present study is to examine critically from ethical and theological perspectives the semantic method Izutsu applies to the Qur‟ānic key-concepts in his two works, God and Man in the Qur’an and Ethico-Religious Concepts in the Qur’an.